2021
DOI: 10.1155/2021/5629067
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Etiological Analysis of Gastroesophageal Reflux Disease by Gastric Filling Ultrasound and GerdQ Scale

Abstract: Objective. To investigate the diagnosis and etiological analysis of GERD by gastric filling ultrasound and GerdQ scale. Methods. The clinical data of 100 suspected GERD patients were selected for retrospective analysis. The selection time was from June 2016 to June 2019. According to the gold standard (endoscopy) results, they were divided into the gastroesophageal reflux group (positive, n = 62) and the nongastroesophageal reflux group (negative, n = 38); both gastric filling ultrasound and GerdQ scale examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“… 17 , 19–21 A recent study in China showed that the sensitivity and specificity of GERDQ were 90.30% and 92.10% for GERD diagnosis, respectively. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 19–21 A recent study in China showed that the sensitivity and specificity of GERDQ were 90.30% and 92.10% for GERD diagnosis, respectively. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 16 GERD was diagnosed in participants with a score of ≥ 8 on the evaluation of GERDQ. 16 , 18 All participants in the population with a score of < 8 on the evaluation of GERDQ were used as control participants in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…15 The flow diagram of study selection is presented in Figure 1. Twelve of the studies were prospective studies, while the remainder was a cross-sectional study 16 and a retrospective study 17 ; more than half (8/14) of the studies were done in Asian countries, [15][16][17][18][19][20][21][22] while the rest were mostly from Western countries 2,23-27 (Table 1). For the reference test, five studies used only upper endoscopy, [15][16][17][18]22 four studies used only pH monitoring/ impedance, 19,23,26,27 and five studies used both upper endoscopy and pH monitoring/impedance 2,20,21,24,25 (Table S3).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Twelve of the studies were prospective studies, while the remainder was a cross-sectional study 16 and a retrospective study 17 ; more than half (8/14) of the studies were done in Asian countries, [15][16][17][18][19][20][21][22] while the rest were mostly from Western countries 2,23-27 (Table 1). For the reference test, five studies used only upper endoscopy, [15][16][17][18]22 four studies used only pH monitoring/ impedance, 19,23,26,27 and five studies used both upper endoscopy and pH monitoring/impedance 2,20,21,24,25 (Table S3). Studies using only upper endoscopy as the reference test can differentiate ERD and non-ERD, studies using only pH monitoring/impedance can only detect abnormal acid exposure, while studies utilizing both upper endoscopy and pH monitoring/impedance can detect ERD, NERD, and normal patients.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…It is precisely because of the above reasons that before the 1980s, it was agreed at home and abroad that the ultrasound examination of the gastrointestinal tract was basically a blind spot [ 8 ], which did not receive due attention and development. It was not until the introduction of gastrointestinal ultrasound contrast agents, which greatly improved the imaging performance of gastrointestinal ultrasound, that gastrointestinal ultrasound was rapidly applied and developed, and gradually became an important means of diagnosing gastrointestinal diseases, Wang et al [ 9 ] pointed out that gastric filling ultrasonography has a high diagnostic value in gastroesophageal reflux disease. Currently, gastric filling ultrasonography (GFUS) has been widely used in the preoperative evaluation of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%